The New Nancy : Flexible and Relatable Daily Comics in the Twenty-First Century - Karnicky, Jeffrey (Book collections on Project MUSE., 2023)
"In The New Nancy Jeff Karnicky explores how successful today's daily comic strips are flexible and relatable, and he uses Olivia Jaimes's 2018 reboot of the long-running comic strip Nancy to illustrate the ways that contemporary comics have adapted to twenty-first-century technology and culture. Because comic creation has become part of the gig economy, flexible comics must be accessible to both online and print readers, and they must quickly grab readers' attention. Flexible comic creators like Jaimes must focus both on the work of producing comics and on building an audience. Daily comics also must form a relatable connection with readers. Most contemporary comic creators cultivate an online persona through which they engage readers with specific identities, beliefs, and expectations. This work might form a mutually beneficial bond that results in a successful daily comic strip, but it risks becoming fraught, toxic, and sometimes even dangerous. Olivia Jaimes cultivates a relatable persona in connection with longtime readers and new fans. And Nancy is funny-the strip finds its humor in both nostalgic objects (like cookie jars) and contemporary technological objects (like smartphones). Rebooted comic strips like Nancy directly confront the stereotypical representations that haunt the past of comics. Focusing on Nancy's role in contemporary culture, Karnicky uses literary studies, cultural studies, and media studies to argue that Olivia Jaimes's comic strip has something to say about comics, contemporary culture, and the intersection of the two. "--